Réponses

Meilleure réponse !
  • Utilisateur Brainly
2014-02-05T17:40:44+01:00
A= (9x-7)²
A= 81x²-126x+49

B= (x+9)(11-5x)
B= 11x-5x²+99-45x
B= -5x²-34x+99

C= (2x-3)(2x+3)
C= 4x²-9

D= (11+8x)²
D= 121+176x+64

E= (x+1)² +7x(2-x)
E= x²+2x+1+14x-7x²
E= -6x²+16x+1

F= (x+3)(2x-1) - 3x(2x+5)
F= 2x²-x+6x-3 - (6x²+15x)
F= 2x²-5x-3 - 6x²-15x
F= -4x²-20x-3

G= (4t+1)(4t-1) - (3t+2)²
G= 8t²-1 - 9t²-12t-4
G= -t²-12t-5

H= 2(s+5)(s-5)+(4s+3)²
H= 2(s²-25)+8s²+24s+9
H= 2s²-50+8s²+24s+9
H= 10x²+24s-41

I= (3x+4)² - (1-2x)(6+x)
I= 9x²+24x+16 - (6+x-12x-2x²)
I= 9x²+24x+16-6-x+12x+2x²
I= 11x²+35x+10